Long Term Outcomes of Freestyle Stentless Aortic Bioprosthesis: A Single Center Experience - (:unkn) unknown (My University, 2020)
Background: The study is presenting our long-term clinical results after freestyle stentless aortic root bioprosthesis replacement in patients with severe aortic insufficiency with ascending aortic aneurysm. Methods: Seventy-seven patients with ascending aortic aneurysms and aortic valve insufficiency underwent a total root replacement procedure using a stentless “Freestyle” valve (Medtronic Inc., Minneapolis, Minnesota). There were 50 (64.9%) men and 27 (35.1%) women. Mean age was 68.7 ± 11.1 years. The surgical procedure used a complete root replacement. Concomitant procedures included coronary artery bypass grafting in 15 (19.5%) patients. Results: The mean cardiopulmonary bypass time was 130.3 ± 26.4 minutes and total aortic cross clamp time was 99.5 ± 23.6 minutes. Hospital mortality was 2.6%. The median follow-up time was 11.2 years. The 5- and 10-years freedom from aortic valve reoperation were 97.4 ± 1.2% and 93.4 ± 4.9%, respectively. During 10 years follow up, there were 14 late deaths; 4 deaths were cardiac, and 10 deaths were noncardiac. Valve-related deaths were attributable to thromboembolism in 1 patient, endocarditis in 2 patients, and congestive heart failure in 1 patient. Conclusion: The freestyle stentless aortic root bioprosthesis offered good clinical outcomes, in terms of survival and structural valve deterioration. The Freestyle valve is a viable option for use in patients undergoing bioprosthetic aortic valve replacement and expected desire for long-term durability.
Long Term Outcomes of Freestyle Stentless Aortic Bioprosthesis